INTENSITAS NYERI DAN PARITAS DENGAN KEPATUHAN MELAKUKAN MOBILISASI DINI PADA IBU POST PARTUM SC (SECTIO CAESAREA) HARI PERTAMA DI RS AURA SYIFA KABUPATEN KEDIRI TAHUN 2016 - Galuh Pradian Y; Rizca Paramita A (STRADA : Jurnal Ilmiah Kesehatan, 2017)
Early mobilization is one of the basic concepts in treatment of puerperal few hours after sectio caesraea to accelerate healing of the surgical wound. In the implementation of compliance in conducting early mobilization post SC influenced by several things.This research is an analytic correlation with cross sectional approach. The populat ion in this study were all post partum SC mothers first day in postpartum room Samples are 23 peoples, Instruments in this study using observation sheet. Results were analyzed by multiple logistic regression statistical test. The results showed that most respondents experiencing severe pain controlled (52.2%), nearly half are primiparous (48%) and the majority of non-compliance (65.2%) in conducting early mobilization post SC on the first day after his operation. With multiple logistic regression statistical test (α = 0.05%), Odd Ratio (OR) obtained 1.013 with a P-value of 0.003. There is a correlation between intensity of pain and parity with compliance doing early mobilization of maternal post partum sc (sectio caesarea) first day in the Aura Syifa Hospital Kediri 2016, where the intensity of the pain is more dominant than the parity and affect 1,013 times the adherence mother did early mobilization post SC on the first day. Expected post partum mothers SC not to be lazy to do early mobilization after surgery.